Determination of cefalexin in wastewater by ultra-performance liquid chromatography with photodiode array detector - Nguyen, Huy Hoài; Nguyen, Văn Hợp (Journal of Technical Education Science, 2016)
The Ultra Performance Liquid Chromatography method has been developed for the determination of cefalexin in wastewater samples. The chromatography was performed by ACQUITY UPLC with Cortecs-C18 column using a mobile phase containing the mixture of methanol R, acetonitrile R, 13.6 g/l solution of potassium dihydrogen phosphate R and water R in the ratio of 2:5:10:83 (v/v), at a flow rate 0,3 ml/min and a UV-PDA detector. The statistical data analysis of the method such as the specificity, sensitivity, linearity, precision, accuracy, giving results within the acceptable range. Linearity for cefalexin concentrations was established in the range of 4 - 60 µg/L. The limits of detection (LOD) and the limits of quantification (LOQ) were found to be 1.2 µg/L and 4.0 µg/L, respectively. The method has showed the advantages of the Ultra Performance Liquid Chromatography for determination of cefalexin in wastewater at very low concentration levels (µg/L).